Spatial Development and the Expanding European Integration of the Hungarian Banking System - Gál, Zoltán (Discussion Papers, 2012)
The paper is concerned with the development stages and the spatial transformation of the Hungarian banking system in the economic transition & post-transition peri¬ods. It gives an overview of the development tendencies of the financial re-integra¬tion into the global market and particularly concentrates on the spatial polarisation factors (concentration - de-concentration; centralisation - decentralisation) which affect banking. The paper explores the arguments behind the extremely high cen¬tralisation of headquarter functions in Budapest and the factors that have impact on the establishment of locally-regionally based banks. This is followed by an intro¬duction of the different organisational (institutional) and territorial (location strate¬gies) level of the Hungarian banking system, dealing with either the domestic or the international financial central-function of Budapest and the reorganisation of the bank network and with its social consequences (financial exclusion) in the re¬gions. The paper argues that EU membership is not a dramatic event in the integra¬tion process of the Hungarian banking sector, partly due to its particular ownership structure, the integration of the banking sector has already taken place. The paper concludes that the EMU integration could have been affected more adversely the Hungarian regions already characterised by the endogenous disparities, which are to a large extent rooted in the deficiency of their financial base.